A Stereotype in Jay Chou's "Snake Dance" as a cross-cultural phenomenon in contemporary mandopop - Li, Fan; Chow, Ow Wei (Immigrant Institutet, 2023)
Certain typical elements of ancient Egyptian culture have already become particularly symbolically charged. Even today, this sort of fascination for ancient Egypt and its relevant things still exists. Many different showing examples of ancient Egyptian culture in a variety of domains around the world demonstrate peoples continued interest in it. This article discusses a song which was composed by Jay Chou, titled "Snake Dance", and as a pertinent example in Mandopop, how popular music and Jay Chous creative style were intertwined with the cognition of ancient Egypt. It demonstrates how this song directly reflects the features related to the stereotype in cross-cultural communication. Through textual and visual analysis in terms of lyrics, music, and music video, this article shows the connection between already existing examples in contemporary Mandopop under the context of global cross-cultural phenomenon, especially the holistic presentation of this form of Egyptian elements observed. This study also aims to fill the previously cross-cultural research gap while explaining an acceptable form of blending ancient Egyptian elements in Mandopop.